Linoleic acid, but not cortisol, stimulates accumulation of casein by mouse mammary epithelial cells in serum-free collagen gel culture. - Levay-Young, B K (1987)
A two-step culture system has been developed to analyze the role of hormones in casein accumulation by mammary epithelial cells obtained from adrenalectomized and ovariectomized adult virgin mice. In the first step cells are grown inside collagen gel in medium containing insulin, epidermal growth factor (EGF), and linoleic acid for 9 days; these conditions stimulate very little casein accumulation. Following this growth phase the gels are released to float in medium containing insulin, prolactin, and linoleic acid. During this second phase the mammary cells will accumulate large amounts of casein, but only in the simultaneous presence of insulin, prolactin, and linoleic acid; in the absence of linoleic acid casein accumulation is greatly reduced. The casein accumulation is not dependent on the presence of the glucocorticoid cortisol and will occur in spite of the presence of the antiglucocorticoid agent RU 38 486. To determine if the response to cortisol observed in organ culture by other investigators might be mediated by stromal cells, epithelial cells were grown in collagen gel under fatty acid-free conditions and then cocultured with explants of mammary fat pads from adult virgin mice with or without mammary parenchyma. The cocultures were performed in fatty acid-free medium containing insulin and prolactin with or without cortisol. In the majority of experiments the mammary epithelial cells in the collagen gel accumulate more casein in the presence of cortisol than in its absence, irrespective of the presence of mammary parenchyma in the explant. Thus, mammary epithelial cells are directly dependent on insulin and prolactin for casein accumulation and indirectly dependent on cortisol by means of its effect on the stromal cells. This cortisol effect may be to cause release into the medium of linoleic acid or a metabolic product of linoleic acid from the stromal cells.